Peningkatan Literasi Gizi melalui Edukasi Label Informasi Nilai Gizi di Posyandu Limau Manis Selatan Kota Padang: Strengthening Nutrition Literacy Through Education on Nutrition Labels at Posyandu Limau Manis Selatan, Padang City - Yosi Irene Putri; Adisti Larasati; Azrimaidaliza; Tri Widi Astuti; Nadya Rahma Putri; Erle Mabel Fadhlul Rohman (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Non-communicable diseases (NCDs) remain a major global health challenge, including in Indonesia. Healthy and balanced diet is one of the key strategies to prevent NCDs. Nutrition literacy, defined as the ability to understand and apply nutritional information in daily life, includes the skill of interpreting nutrition facts labels on packaged foods. The skill to read and use nutrition facts labels is associated with healthier eating patterns and improved food choices. This community service program aimed to enhance mothers’ knowledge of nutrition facts labels and to encourage the practical application of this knowledge by choosing healthier food products based on the nutrition labels provided. The activity was conducted at Puskesmas Ulu Gadut on October 17, 2025, involving 30 participating mothers, since mothers usually are the ones who are responsible for deciding the consumption of the household. s. The intervention includes preparation, implementation, and evaluation phases. Activities consisted of health education sessions, discussion, and distribution of leaflets and posters about how to read nutrition facts labels. At the evaluation phase, participants were asked to compare two similar food products and choose which one is healthier based on their nutrition contents showed on the nutrition labels. From all the products given, all participants could choose correctly and explain the reasons for their choice. The activity proved effective in increasing awareness of reading nutrition labels to make healthier food decisions. It is recommended that this program could be applied to other age groups and further developed media for a more sustainable impact.